2022
DOI: 10.5539/elt.v15n9p138
|View full text |Cite
|
Sign up to set email alerts
|

Academic Vocabulary Acquisition Difficulties for Saudi Postgraduate Students in New Zealand Universities

Abstract: Education outcomes for L2 students in academic preparation programs, undergraduate studies, and graduate work are directly influenced by the learning and use of academic vocabulary. Among 15 Saudi graduate students studying in New Zealand, this study investigated at their perspectives with academic vocabulary learning. Students in Saudi Arabia who are enrolled at New Zealand universities were asked about their difficulties in learning academic vocabulary. According to this study, a new perspective on academic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In most cases, ESL post-secondary learners are expected to acquire academic words incidentally through reading activities. Albeit providing good lexical input (Nation, 2013), reading academic materials alone may not be very reliable for ESL learners to learn academic words (Aldawsari, 2017;Gallagher et al, 2019;Sulaiman et al, 2018); since this incidental approach has a low pick-up rate (Schmitt, 2008). Moreover, textbooks often include words that appear once without repetition, a vital element for vocabulary acquisition (Nation, 2013).…”
Section: Challenges In Learning the Academic Vocabularymentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, ESL post-secondary learners are expected to acquire academic words incidentally through reading activities. Albeit providing good lexical input (Nation, 2013), reading academic materials alone may not be very reliable for ESL learners to learn academic words (Aldawsari, 2017;Gallagher et al, 2019;Sulaiman et al, 2018); since this incidental approach has a low pick-up rate (Schmitt, 2008). Moreover, textbooks often include words that appear once without repetition, a vital element for vocabulary acquisition (Nation, 2013).…”
Section: Challenges In Learning the Academic Vocabularymentioning
confidence: 99%
“…In this regard, it is necessary to adopt a more direct, explicit and purposeful and systematic approach to academic vocabulary learning among ESL postsecondary learners (Aldawsari, 2017;Coxhead, 2021;Yunus et al, 2016). Taking into consideration the Malaysian Education Blueprint's 7 th shift regarding the use of Information Communication Technology (ICT) (MOE, 2015), it is apt for explicit academic vocabulary instructions to integrate technology.…”
Section: Introductionmentioning
confidence: 99%
“…Paraphrasing is another aspect of area students may find difficult [23,[53][54][55]. Although paraphrasing is an effective writing strategy used to synthesize significant information from multiple sources, it requires the writer to be well-equipped with a thorough understanding of what they have read beyond linguistic interpretation [56].…”
Section: An Overview Of the Theoretical Frameworkmentioning
confidence: 99%
“…Recent research on Saudi Arabian ESL students' writing enhancement progress has revealed an unsatisfactory result (Mould, 2010;Grami & Alzughaibi, 2012;Abduljawad, 2021;Ankawi, 2022;Ansari, 2023). Moulds's (2010) and Abduljawad's (2021) findings showed that the impact of the first language and the insufficient exposure to English in ESL classrooms deter students from achieving high grades in English writing exams.…”
Section: Introductionmentioning
confidence: 99%
“…They achieve high marks in portfolio evaluations, in contrast to their performance in the final writing examination. Therefore, a significant proportion of students hold unfavorable perceptions of their writing abilities as they fail to perceive themselves as effective in the final examinations (Ankawi, 2022). There is an explicit research gap between students' results in the writing examination and in the writing portfolio.…”
Section: Introductionmentioning
confidence: 99%